Приближенный расчет магнитного момента Земли - Баранов, Михаил Иванович (НТУ "ХПИ", 2010)
Предложена приближенная формула для расчетного определения магнитного момента Земли, базирующаяся на новой модели внутреннего электрического источника постоянного геомагнитного поля. Данный электрический источник на современном геофизическом этапе развития Земли основан на естественных круговых коаксиальных избыточных электронных (отрицательных) токах вращающейся совместно с твердой корой наружной сферической части полужидкой электропроводящей мантии Земли. Результаты численной оценки по предложенной формуле магнитного момента Земли и их сравнение с имеющимися экспериментальными данными свидетельствуют о об их хорошей корреляции

An approximate formula for calculating magnetic moment of the Earth is introduced, the formula based on a new model of internal electric source of the permanent geomagnetic field. This electric source, at the present geophysical stage of the Earth development, is based on natural circular coaxial excess electron (negative) currents of the semifluid electroconducting Earth mantle that is rotating with the crust of the outer spherical part. Results of numeral estimation of the magnetic moment of the Earth with the formula presented and their comparison with available experimental information testify their good correlation
Approximate calculation of magnetic moment of the Earth
Keywords: электрический источник; постоянное геомагнитное поле; геофизический этап развития; электропроводящая мантия; semifluid mantle; liquid core of the Earth; circular electron currents; Earth mantle; permanent magnetic field; magnetic moment of the Earth